The Future of Work: New Underclass, Dystopian Reality? - Jayakumar, Shashi (2017)
The dust will take decades to settle on the key issue of precisely how much technology and artificial intelligence (AI) will displace human labour. It is clear the near future will see a sizeable proportion of jobs worldwide threatened and substituted by automation, machine learning, or both. What does this mean for national security?